Associations between monthly temperature anomalies and mortality among children younger than five years in low- and middle-income countries - Pengfei Li; Jingyi Wu; Tao Xue; Tong Zhu (Communications Medicine)
Abstract Background This study examined associations between anomalous temperatures and under-five mortality (U5M) in low- and middle-income countries (LMICs). Methods Between 1998 and 2019, data were collected on 1,745,132 live births across 56 LMICs. The median age was 27.0 months (interquartile range: 12.0, 43.0), and 51.0% were male. Monthly temperature anomalies were calculated as deviations from the long-term average temperature for the same calendar months. We developed a two-dimensional exposure-response function (ERF) based on a varying-coefficient model to examine the relationship between U5M and both long-term average temperatures and anomalous temperatures. Results Here we show, in the multicenter model, each 1 °C increase in positive temperature anomalies or decrease in negative temperature anomalies is associated with an 8% (95% confidence interval [CI]: 6%, 11%) or 2% (95% CI: −1%, 4%) excess risk of U5M, respectively. The two-dimensional ERF reveals considerable heterogeneity in the impact of anomalous temperatures on U5M across different temperature zones. Positive temperature anomalies pose a significant hazard to children in warm and hot zones, whereas negative anomalies are primarily hazardous in cold zones but appear protective in hot zones. The sibling-matched model demonstrates nonlinear and heterogeneous effect estimates consistent with the multicenter model findings. Conclusions Anomalous temperatures of both heat and cold are associated with an increased risk of child mortality in LMICs, with the effect varying by temperature zone, reflecting the adaptive capacity of populations to local climates. There is an urgent need to develop regionally adaptive strategies to protect child health amid global climate change.